1997 Annual Meeting of the North American Fuzzy Information Processing Society - NAFIPS (Cat. No.97TH8297)
DOI: 10.1109/nafips.1997.624073
|View full text |Cite
|
Sign up to set email alerts
|

Applications of fuzzy logic to software metric models for development effort estimation

Abstract: Software metrics are measurements of the software development process and product that can be used as variables (both dependent and independent)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 11 publications
0
30
0
Order By: Relevance
“…Although their published empirical analyses are not extensive (given the early stage of the research), their work does highlight the significant potential in fuzzy logic modeling when applied to aspects of software project management. Our own work (Gray and MacDonell 1997b;MacDonell et al 1999) has similarly indicated the applicability of fuzzy logic methods to this domain -one of the aims of the work described here is to provide empirical evidence in support of this.…”
Section: Modeling Aspects Of Software Project Managementmentioning
confidence: 61%
“…Although their published empirical analyses are not extensive (given the early stage of the research), their work does highlight the significant potential in fuzzy logic modeling when applied to aspects of software project management. Our own work (Gray and MacDonell 1997b;MacDonell et al 1999) has similarly indicated the applicability of fuzzy logic methods to this domain -one of the aims of the work described here is to provide empirical evidence in support of this.…”
Section: Modeling Aspects Of Software Project Managementmentioning
confidence: 61%
“…Study showed that fuzzy logic model has a place in software effort estimation [2]. Using real project data, Gray and MacDonell compared Function Point Analysis, Regression techniques, feedforward neural network and fuzzy logic in software effort estimation.…”
Section: Fuzzy Logic In Software Effort Estimationmentioning
confidence: 99%
“…There are a number of problems with the existing effort estimation models [2,23,24,14]. Firstly most prediction models required highly accurate estimates to be supplied as input into the models.…”
Section: Why Fuzzy Logic?mentioning
confidence: 99%
See 1 more Smart Citation
“…Fuzzy logic has recently gained a greater amount of attention in the software metrics literature as a means for solving some of these long-standing problems [2,3]. Obviously fuzzy logic is not a panacea for all of project management's ills.…”
Section: Fuzzy Logic For Software Metric Modelsmentioning
confidence: 99%